PEMBELAJARAN TEMATIK INTEGRATIF DI KELAS IV SEKOLAH DASAR NEGERI 66 PONTIANAK KOTA - Bernadetha Bella Korina; Tahmid Sabri; Sugiyono Sugiyono (Universitas Tanjungpura, 2020)
AbstractThis research is a descriptive qualitative research. This study aims to describe the integrative thematic learning planning in class IV 66 Pontianak City Primary School and describe the implementation of integrative learning in class IV Pontianak City Primary School 66. To achieve these objectives, research uses descriptive qualitative research methods. Data collection techniques using observation, interviews and documentation using triangulation techniques to test the validity of the data. Data analysis using the model of Miles and Hubberman, namely data reduction, data display and conclusion drawing. The results of the study show that: (1) integrative thematic learning planning conducted by teachers has been carried out in accordance with the Minister of Education and Culture Regulations educational process standards Number.22 of 2016 by making syllabus and lesson plans before the learning process (2) the implementation of integrative thematic learning undertaken by teachers ie starting with activities introduction, the core activities using a scientific approach and closing activities have been carried out in accordance with Minister of Education and Culture Regulations Number.22 of 2016. Keywords: Learning, Integrative Thematic Learning.